1998
DOI: 10.1097/00000374-199811000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Levels in Ethanol-Naive Alcohol-Preferring and Nonpreferring Rats and in Wistar Rats after Ethanol Exposure

Abstract: Neuropeptide Y (NPY) is a hexatriacontapeptide amide that is now well characterized as a neuromodulator in the central nervous system (CNS). When infused into the CNS, NPY produces both anxiolytic and orexigenic effects. NPY's anxiolytic effects appear to be mediated through receptors in the central amygdala, whereas its orexigenic effects are localized in discrete hypothalamic nuclei. Both food restriction and food deprivation produce increased levels of the peptide in the hypothalamus that are ameliorated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 0 publications
8
88
1
2
Order By: Relevance
“…Ntf5, but not Ntf3 has been shown to stimulate the expression of Npy in the rat neocortex (Wirth et al, 1998). The findings indicating lower expression of Npy in the iP than iNP rats are in general agreement with reports on tissue levels of NPY reported for the selectively bred P and NP lines (Ehlers et al, 1998;Hwang et al, 2004). A brief survey of other genes connected to Npy reveals that the products of Reln and Npy5r also interact with Npy.…”
Section: Overall Strain Differencessupporting
confidence: 85%
See 1 more Smart Citation
“…Ntf5, but not Ntf3 has been shown to stimulate the expression of Npy in the rat neocortex (Wirth et al, 1998). The findings indicating lower expression of Npy in the iP than iNP rats are in general agreement with reports on tissue levels of NPY reported for the selectively bred P and NP lines (Ehlers et al, 1998;Hwang et al, 2004). A brief survey of other genes connected to Npy reveals that the products of Reln and Npy5r also interact with Npy.…”
Section: Overall Strain Differencessupporting
confidence: 85%
“…P rats have reduced serotonin (5-HT) and dopamine (DA) innervations (Zhou et al, 1991(Zhou et al, ,1994a(Zhou et al, ,1994b(Zhou et al, ,1995, as well as differences in 5-HT (McBride et al, 1993a(McBride et al, ,1997Wong et al, 1993), DA (McBride et al, 1993b), and opioid Strother et al, 2001) receptors. Furthermore, neuropeptide Y (NPY) (Ehlers et al, 1998), corticotropin-releasing factor (Ehlers et al, 1992), neurotensin (Ehlers et al, 1999), substance P, and neurokinin levels (Slawecki et al, 2001) are all significantly lower in CNS regions of P compared to NP rats. Additionally, higher functional neuronal activity has been found in numerous brain regions of the P rat compared to the NP rat (Smith et al, 2001;Strother et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest a role for the amygdala, but not the PVN, in mediating the suppressive effects of NPY on ethanol drinking. Consistent with this notion, lower NPY tissue concentrations in the amygdala are correlated with selection for alcohol preference in both P and HAD1 selectively bred lines of rats (Ehlers et a., 1998;Hwang et al, 1999). In spite of the mutual exclusivity of these pathways and the behaviors they mediate, it is intriguing that the sensitized effects of NPY during ethanol abstinence extend to multiple behaviors.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 78%
“…Quantitative trait locus analyses run on these rats suggested that line differences in ethanol intake may be modulated by the NPY gene (Carr et al, 1998). Furthermore, NPY levels were found to be low in several brain regions of the AP rats, including the central nucleus of the amygdala (CeA) (Ehlers et al, 1998;Hwang et al, 1999). More recently, the selectively bred high alcohol-drinking (HAD) rats also were found to have abnormally low levels of NPY in the CeA (Hwang et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we assessed coexpression of cFLI with tyrosine hydroxylase (TH) (the rate-limiting enzyme in catecholamine biosynthesis) in the brainstem. Furthermore, we examined coexpression of ethanolinduced cFLI with neuropeptide Y (NPY), a neuropeptide that is coexpressed with catecholamines in the brainstem (Everitt et al, 1984;Sawchenko et al, 1985) and that recently has been implicated in modulating sedative effects produced by ethanol and voluntary ethanol consumption (Ehlers et al, 1998;Hwang et al, 1999;Thiele et al, 1998a).…”
mentioning
confidence: 99%